2016
DOI: 10.1111/1753-6405.12508
|View full text |Cite
|
Sign up to set email alerts
|

Seroprotection to vaccine‐preventable diseases among workers at a Victorian tertiary hospital

Abstract: Objective: To determine seroprotection for the vaccine‐preventable diseases (VPDs) measles, mumps, rubella, varicella and hepatitis B among new employees seen at a Victorian tertiary hospital staff clinic. Methods: Employees who presented to the staff clinic for immunisation assessment between 1 January 2012 and 31 December 2013 were included. Demographic data, self‐reported disease history and previous vaccination status were reviewed retrospectively to determine impact on serological results. Results: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…A quarter of the HCW did not have IgG against at least one of the MMR components, which is in accordance with findings from Finland, where a quarter (39/157) of paediatric nurses had inadequate immunity to measles, mumps or rubella [4]. Lack of immunity was highest in the youngest HCW, a finding consistent with other studies [5][6][7]. IgG antibodies after disease are often higher than after vaccination [3,20].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A quarter of the HCW did not have IgG against at least one of the MMR components, which is in accordance with findings from Finland, where a quarter (39/157) of paediatric nurses had inadequate immunity to measles, mumps or rubella [4]. Lack of immunity was highest in the youngest HCW, a finding consistent with other studies [5][6][7]. IgG antibodies after disease are often higher than after vaccination [3,20].…”
Section: Discussionsupporting
confidence: 90%
“…Varicella immunity was high with only eight (1.4%) seronegative HCW. Almost all were immune because of previous infection which may explain why their seroprevalence was higher than that found in vaccinated individuals [7,20].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…When not protected against vaccine-preventable diseases, they pose a risk to themselves and their patients, especially in an outbreak situation. Alarmingly, several studies have reported lacking immunity against vaccine-preventable diseases in HCWs [1][2][3].…”
mentioning
confidence: 99%
“…workers and patients. [2][3][4] Therefore, vaccination as well as following the protection measures against infections is important for healthcare workers to decrease the spread of infectious diseases and prevent transmission to other people.…”
Section: Discussionmentioning
confidence: 99%